Situated narratives and sacred dance : performing the entangled histories of Cuba and West Africa - Crosby, Jill Flanders; Torres, J. T. (University of Florida Press, 2021)
"Through a revolutionary ethnographic approach that foregrounds storytelling and performance, this book explores shared ritual traditions between the Anlo-Ewe people of West Africa and their descendants, the Arará of Cuba, who were brought to the island in the Atlantic slave trade"--